2023
DOI: 10.1002/adma.202210201
|View full text |Cite
|
Sign up to set email alerts
|

A pH‐Activatable Copper‐Biomineralized Proenzyme for Synergistic Chemodynamic/Chemo‐Immunotherapy against Aggressive Cancers

Abstract: Artificial enzymes have demonstrated therapeutic benefits against diverse malignant tumors, yet their antitumor potencies are still severely compromised by non‐selective catalysis, low atomic‐utilization efficiency, and undesired off‐target toxicity. Herein, it is reported that peroxidase‐like biomineralized copper (II) carbonate hydroxide nanocrystals inside single albumin nanocages (CuCH‐NCs) act as a pH‐activatable proenzyme to achieve tumor‐selective and synergistic chemodynamic/chemo‐immunotherapy against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…96 In addition to immunotherapy targeting TNBCs (Fig. 6A), pH-activatable proenzymes have been reported by T. Li et al 97 Albumin nanocages were lled with copper(II) carbonate hydroxide NCs (CuCH-NCs). For the synthesis and application of (CuCH-NCs), biomineralization took 120 min.…”
Section: Immunomodulation and Immunotherapy Through Nanocrystalsmentioning
confidence: 95%
“…96 In addition to immunotherapy targeting TNBCs (Fig. 6A), pH-activatable proenzymes have been reported by T. Li et al 97 Albumin nanocages were lled with copper(II) carbonate hydroxide NCs (CuCH-NCs). For the synthesis and application of (CuCH-NCs), biomineralization took 120 min.…”
Section: Immunomodulation and Immunotherapy Through Nanocrystalsmentioning
confidence: 95%
“…These data showed that FL NPs-induced CDT efficiently promoted cell apoptosis. In contrast, the percentage of apoptotic cells increased to 57.68% in the DOX@FL-treated group, indicating that DOX@FL had a significantly enhanced cell-killing effect. …”
mentioning
confidence: 98%
“…Figure2dshows that the addition of IPA (1 mM) strongly inhibited the antibacterial rate, demonstrating that hydroxyl radicals generated by photocatalysis-self-Fenton of FQM made a stronger relative contribution. Additional ESR studies were conducted to detect the •OH generated pathway in the FQM system 31. Figure 2f showed the obvious •OH (1:2:2:1), •O 2 − (six peaks), and H 2 O 2 signals with the extension of light treatment.…”
mentioning
confidence: 99%